2000
DOI: 10.1103/physrevlett.85.5432
|View full text |Cite
|
Sign up to set email alerts
|

Optically Injected Spin Currents in Semiconductors

Abstract: We show that quantum interference of one and two photon absorption from a two color field allows one to optically inject ballistic spin currents in unbiased semiconductors. The spin currents can be generated with or without an accompanying electrical current and can be controlled using the relative phase of the two colors. We characterize the injected spin currents using symmetry arguments and an eight-band Kane model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
226
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 197 publications
(238 citation statements)
references
References 17 publications
9
226
3
Order By: Relevance
“…It has also been shown that it can induce photocurrents. Here, however, in contrast to the well-known photocurrents caused by quantum interference of one-and two-photon absorption processes in two color light, [8][9][10][11] the photocurrent is due to quantum interference in the elementary one-photon absorption process.…”
mentioning
confidence: 84%
“…It has also been shown that it can induce photocurrents. Here, however, in contrast to the well-known photocurrents caused by quantum interference of one-and two-photon absorption processes in two color light, [8][9][10][11] the photocurrent is due to quantum interference in the elementary one-photon absorption process.…”
mentioning
confidence: 84%
“…19,20 Expressions such as (4) and (8) can also be written for carrier spin polarization and spin current. 22 The interference terms of these describe '1+2' spin control 21 and '1+2' spin current injection, 13 which can be written in terms of material response pseudotensors ζ ijkl…”
Section: Preliminariesmentioning
confidence: 99%
“…43,69 However, we neglect such nonlocal corrections, as has been the practice in previous calculations of coherent control effects. 11,13,19 The initial state is the "vacuum" |0 ; it corresponds to completely filled valence bands and empty conduction bands. If the Coulomb interaction were neglected in a two-band model consisting of valence (v) and conduction (c) bands, the final states would be of the form a † ck a vk |0 , where the operator a † nk creates an electron in an eigenstate of H B , a Bloch state |n, k with band index n and wavevector k. The photon momentum has been neglected, consistent with the long wavelength approximation.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations